Bilateral posterior shoulder dislocation after electrical shock: A case report. Issue 4 (December 2015) - Ketenci, Ismail Emre; Duymus, Tahir Mutlu; Ulusoy, Ayhan; Yanik, Hakan Serhat; Mutlu, Serhat; Durakbasa, Mehmet Oguz
Abstract: Introduction: Posterior dislocation of the shoulder is a rare and commonly missed injury. Unilateral dislocations occur mostly due to trauma. Bilateral posterior shoulder dislocations are even more rare and result mainly from epileptic seizures. Electrical injury is a rare cause of posterior shoulder dislocation. Injury mechanism in electrical injury is similar to epileptic seizures, where the shoulder is forced to internal rotation, flexion and adduction. Presentation of case: This report presents a case of bilateral posterior shoulder dislocation after electrical shock. We were able to find a few individual case reports describing this condition. The case was acute and humeral head impression defects were minor. Our treatment in this case consisted of closed reduction under general anesthesia and applying of orthoses which kept the shoulders in abduction and external rotation. A rehabilitation program was begun after 3 weeks of immobilization. After 6 months of injury the patient has returned to work. 20 months postoperatively, at final follow-up, he was painless and capable of performing all of his daily activities. Discussion: The amount of bilateral shoulder dislocations after electrical injury is not reported but is known to be very rare. The aim of this case presentation is to report an example for this rare entity, highlight the difficulties in diagnosis and review the treatment options. Conclusion: Physical examination and radiographic evaluation are important for quick and accurate diagnosis. Highlights: Posterior dislocation of the shoulder is a rare and commonly missed injury. Electrical injury is a rare cause of posterior shoulder dislocation. Physical examination and radiographic evaluation are important for quick and accurate diagnosis. If the diagnosis is made early and the humeral head impression defect is less than 25%, closed reduction followed by a good rehabilitation program can lead to successful results.